FENOMENA, FEMINISME DAN POLITICAL SELF SELECTION BAGI PEREMPUAN - Nurwani Idris - - (Sekolah Pascasarjana Universitas Brawijaya, 2010)
Abstract Democracy needs all participation people in the country, women and men.Â The political right for women, as we know was feminism hard and long time struggled, therefore now the women have the high quality live in politic, the economic and social.Â All the country in the world have ratificated the PBB of law for political freedom for women as the same as men. Especially in Indonesia now thereâ€™s no formal barriers for women leadership, if they select to participate in politics but it was the phenomenon for the women among self selection in politics, the freedom to be participating and children, husband, housing, that still stronger; from which one barrier â€œself selectionâ€ or â€œculture and religionâ€ responsibility where significantly. Minangkabau women, forward analysis we can aim self selection or children, husband and family responsibility.Â It is indisputable that the womenâ€™s awareness and struggle in the politics are debt to the feministsâ€™ endless efforts. The feminists have fostered the women to empower themselves by which they reach equal position compared with their counterparts, in nearly all aspects of the social life. Â Keywords:Â phenomenon, feminism, and political self selection.